Vocational education and training policies: the tension between inclusion, employability and democratization - Alves, Natália (2021)
This communication is part of the research project YOUNG_ADULLLT2. The purpose of this project is to understand the interaction between lifelong learning policies, the life conditions and stages of young adults in situations of vulnerability, and the promotion of social development and inclusion. This communication focuses on the analysis of double certification education and training (VET) provisions (Apprenticeship courses, Professional courses and Adult VET courses), promoted either by regular and Professional schools or public training centres, in the sub-region of the Alentejo Litoral, in Portugal. The analysis of legal frameworks and interviews reveals a tension between three mains aims: the fight against exclusion, the promotion of individual employability and the democratization of school access and success. However, the hegemonic resonant discourse is strongly anchored in a technical-instrumental perspective of education and training, oriented towards employability, and the management of human resources according to the labor market needs.